2007
DOI: 10.1086/512183
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Unusual Dwarf Galaxy in the Outskirts of the Milky Way

Abstract: In this Letter, we announce the discovery of a new dwarf galaxy, Leo T, in the Local Group. It was found as a stellar overdensity in the Sloan Digital Sky Survey Data Release 5 (SDSS DR5). The color-magnitude diagram of Leo T shows two well-defined features, which we interpret as a red giant branch and a sequence of young, massive stars. As judged from fits to the color-magnitude diagram, it lies at a distance of about 420 kpc and has an intermediate-age stellar population with a metallicity of [Fe/H]= -1.6, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
223
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(238 citation statements)
references
References 31 publications
13
223
2
Order By: Relevance
“…Until now, LeoT (d∼420 kpc) has been the closest known low-luminosity dwarf outside the virial radius of the Milky Way. Notably, LeoT retains a significant H I gas reservoir (Irwin et al 2007;Ryan-Weber et al 2008) and has signatures of star formation within the past few hundred Myr (de Jong et al 2008;Weisz et al 2012), but the large gap in distance between the most distant gas-free objects (Leo I and Leo II at 225-250 kpc) and LeoT limits its utility in constraining gas loss mechanisms for Milky Way satellites (see Figure 9). EriII is located in this gap, slightly beyond the virial radius, and has a similar luminosity to LeoT and a higher dynamical mass.…”
Section: Star Formation In Eridanusiimentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, LeoT (d∼420 kpc) has been the closest known low-luminosity dwarf outside the virial radius of the Milky Way. Notably, LeoT retains a significant H I gas reservoir (Irwin et al 2007;Ryan-Weber et al 2008) and has signatures of star formation within the past few hundred Myr (de Jong et al 2008;Weisz et al 2012), but the large gap in distance between the most distant gas-free objects (Leo I and Leo II at 225-250 kpc) and LeoT limits its utility in constraining gas loss mechanisms for Milky Way satellites (see Figure 9). EriII is located in this gap, slightly beyond the virial radius, and has a similar luminosity to LeoT and a higher dynamical mass.…”
Section: Star Formation In Eridanusiimentioning
confidence: 99%
“…This places Eri II in a sharp transition region between the gas-free dwarf spheroidals (with D250 kpc) and the more distant gas-rich star-forming dwarfs (Einasto et al 1974;Blitz & Robishaw 2000;Grcevich & Putman 2009;Spekkens et al 2014). Koposov et al (2015) suggested that Eri II may contain a young stellar population component (∼250 Myr) because a few candidate blue-loop stars are spatially coincident, and therefore EriII would be similar to the gas-rich dwarf Leo T, which is slightly more distant and more luminous (D = 420 kpc, M V ∼−8; Irwin et al 2007;de Jong et al 2008;Ryan-Weber et al 2008) and has undergone multiple epochs of star formation (de Jong et al 2008;Weisz et al 2012). If this were the case, EriII would be the least luminous star-forming galaxy known.…”
Section: Introductionmentioning
confidence: 99%
“…The sample of the known nearby galaxies within a distance of D ∼ 2 Mpc has been collected from the seminal work of G03 and the latest nearby galaxy catalog of Karachentsev et al (2013;K13 hereafter). Our compilation (see Table 5) includes the recently discovered ultra-faint dwarf systems (uFds) around the MW, and faint Andromeda dwarf galaxies (Willman et al 2005a(Willman et al , 2005bBelokurov et al 2006;Zucker et al 2004Zucker et al , 2006aZucker et al , 2006bZucker et al , 2007Irwin et al 2007Irwin et al , 2008Walsh et al 2007;McConnachie et al 2008;Martin et al 2009;Richardson et al 2011;Bell et al 2011;Slater et al 2011), which yields a total of 79 sample dwarf satellite galaxies. We use integrated K-band luminosity (L K ) values (adopted from Table 2 of K13) as the abscissa instead of using absolute V-or B-band magnitudes because the L K is a better tracer for the total mass of a given galaxy (Drory et al 2004).…”
Section: Luminosity-metallicity Relationmentioning
confidence: 99%
“…Following the success of the Sloan Digital Sky Survey (SDSS; York et al 2000), which revealed the presence of "ultra-faint" ( > -M 5 V ) MW satellites (e.g., Willman et al 2005;Belokurov et al 2006;Zucker et al 2006;Irwin et al 2007;Koposov et al 2007;Walsh et al 2007;Balbinot et al 2013;, recent wide-field photometric surveys have been instrumental in finding many more such systems in the MW halo, and probing to increasingly faint levels (e.g., Bechtol et al 2015;Drlica-Wagner et al 2015;Kim et al , 2016Koposov et al 2015a;Laevens et al 2015aLaevens et al , 2015bMartin et al 2015;Luque et al 2016;Torrealba et al 2016aTorrealba et al , 2016b. A growing number of the newly discovered MW satellites are filling the gap between the classical dwarf galaxies and globular clusters in the size-luminosity plane, meaning that it is increasingly difficult to classify these systems using only these two parameters .…”
Section: Introductionmentioning
confidence: 99%